2019
DOI: 10.1021/acsomega.9b00646
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel-Deposited Ti-Doped ZnO: Toward Cell Fouling Transparent Conductive Oxides

Abstract: Ti-doped ZnO thin films were obtained with the aim of tailoring ZnO film bioadhesiveness and making the optoelectronic properties of ZnO materials transferable to biological environments. The films were prepared on silicon substrates by sol–gel spin-coating and subsequent annealing. A Ti–O segregation limits the ZnO crystallite growth and creates a buffer out-layer. Consequently, the Ti-doped ZnO presents slightly increased resistivity, which remains in the order of 10 –3 Ω·cm. The stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The two peaks in the diagram of the TZt300 film are in agreement with the (100) and (002) peak assignments for ZnO crystals in a wurzite structure [2]. In any case, the lattice constriction effects induced by the high concentration of Ti dopant are responsible for an inhibition of the crystallization of ZnO for a given thermal activation, as previously observed [19]. This decrease in the crystal structure by TiO 2 attributed to the higher activation energy required for the crystallization of TiO 2 [30].…”
Section: X-ray Diffractionsupporting
confidence: 89%
See 4 more Smart Citations
“…The two peaks in the diagram of the TZt300 film are in agreement with the (100) and (002) peak assignments for ZnO crystals in a wurzite structure [2]. In any case, the lattice constriction effects induced by the high concentration of Ti dopant are responsible for an inhibition of the crystallization of ZnO for a given thermal activation, as previously observed [19]. This decrease in the crystal structure by TiO 2 attributed to the higher activation energy required for the crystallization of TiO 2 [30].…”
Section: X-ray Diffractionsupporting
confidence: 89%
“…An R vs. C map is presented in Figure 6b and shows the improvement in the electrical conduction for MwPA with respect to TA films as demonstrated by the decreasing resistance. We had previously shown that inclusion of Ti implies an increase in surface resistivity with respect to pure (TA) ZnO [19], so that a MwPA process can partially compensate for this drawback. This confirms the trend of reduced surface resistivity of MwPA samples for MwPA with respect to TA [26].…”
Section: Electrical Optical and Wetting Propertiesmentioning
confidence: 99%
See 3 more Smart Citations